1988
DOI: 10.1007/bf02624183
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant activity of mouse transformed cells: Different expression in freshly isolated or cultured cells

Abstract: This study was originally designed to investigate whether there is any correlation between the type of procoagulant activity (PCA) and the tumorigenicity of transformed cells. The data obtained are relevant to this question and to defining the differences in the expression of cellular activities depending on the in vitro system used. PCA was measured and characterized in normal, immortalized, and tumorigenic mouse fibroblasts. In all the cell lines studied the activity was of tissue factor type, as established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Our study has shown that human cancer cells cultured "in vitro" invariably activate blood clotting through a tissue factorlike procoagulant activity, while cells isolated from human tumor tissues operate through a direct activation of factor X, due to a tumor-associated cysteine protease with the characteristics of cancer procoagulant (9,10). Curatolo et al (13) studied the procoagulant activity of different cell lines of normal, immortalized and tumorigenic mouse fibroblasts and found that in all experiments cultured cells expressed a tissue factor-like activity, while cells freshly isolated from tumor tissues possessed an activity with the characteristics of cancer procoagulant; furthermore, when freshly isolated cells were cultured "in vitro", their activity changed and appeared again to be tissue factor-like. Our data demonstrate a very similar behaviour in human tumor and suggest that the difference in the procoagulant activity of cultured versus freshly isolated cells is a general characteristic of neoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has shown that human cancer cells cultured "in vitro" invariably activate blood clotting through a tissue factorlike procoagulant activity, while cells isolated from human tumor tissues operate through a direct activation of factor X, due to a tumor-associated cysteine protease with the characteristics of cancer procoagulant (9,10). Curatolo et al (13) studied the procoagulant activity of different cell lines of normal, immortalized and tumorigenic mouse fibroblasts and found that in all experiments cultured cells expressed a tissue factor-like activity, while cells freshly isolated from tumor tissues possessed an activity with the characteristics of cancer procoagulant; furthermore, when freshly isolated cells were cultured "in vitro", their activity changed and appeared again to be tissue factor-like. Our data demonstrate a very similar behaviour in human tumor and suggest that the difference in the procoagulant activity of cultured versus freshly isolated cells is a general characteristic of neoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of different studies are often conflicting and the mechanisms by which cancer cells activate the hemostatic system are not completely understood. The reasons for heterogeneity of results may reside in the use of heterologous systems (murine tumors with plasma of other species), in the source of tumor cells ("in vitro" culture or dissociation of tumor tissues) (13), or in the type of tumor material investigated (intact cells or tumor extracts). amino acids, 2 mM L-glutamine and gentamicin.…”
Section: Introductionmentioning
confidence: 99%
“…72 ' 73 One of the perplexing issues that has surfaced in CP research is the diminished, or absent, production of CP in tissue culture. The expression of CP activity in cultured cells is substantially decreased compared with that found in the same tumor cells in vivo 74,75 (Gordon: Unpublished observation). A study was performed to evaluate the CP production by normal and transformed cells in culture, and the levels of activity were vanishingly small.…”
Section: Tumor Cell-specific Procoagulants Cancer Procoagulantmentioning
confidence: 97%
“…Cancer procoagulant may also play a role in the growth and viability of tumor cells [52]. Previous studies have shown that the expression of cancer procoagulant was high in freshly collected cells from solid tumors, but absent in cultured cells, which mainly release tissue factor [53,54]. One possible explanation for this is cooperation of tumor cells and host endothelial cells in vivo produced cancer procoagulant activity [55].…”
Section: Apoptosis In Hypercoagulable Statesmentioning
confidence: 99%